Scaphoid megalourethra associated with congenital urethrocutaneous fistula: a case report of a rare association - Lucas Rossato Chrun; Paulo Acácio Egger; Lia Yoneka Toda; Aquiles Henrique; Orlando Ribeiro Prado Filho; Larissa Rossato Chrun Costa; Victor Hugo Silva Nezo (SpringerOpen, 2023)
Abstract Background Congenital megalourethra is a rare male genital malformation, with less than 100 cases reported in literature. Urethrocutaneous fistula, in turn, has only 65 cases described, which what makes the association between these two anomalies an even rarer condition. Case presentation The patient was male and born at 37 weeks of gestational age. At birth, the testicles were impalpable, and he had a penile malformation compatible with scaphoid megalourethra associated with congenital urethrocutaneous fistula, with urine output exclusively through a small orifice in the ventral region of the penis. When the child completed 7 months and 22 days, underwent the first surgery, laparoscopically. The first Fowler-Stephens was performed, and the gonadal vessels were ligated, with reconstruction of the penis. Nine months later, the second Fowler-Stephens procedure was performed, with bilateral orchidopexy and penoplasty to improve penis aesthetics. The urethra region was not approached. The postoperative period of the second surgery progressed uneventfully. Nowadays, the patient presents adequate urinary stream. Conclusion The scaphoid megalourethra associated with congenital urethrocutaneous fistula is an extremely rare pathology, with very few cases reported in the literature to date. The obstetric USG is important to increasing the chances of early diagnosis and treatment.